2015
DOI: 10.1177/2158244015621598
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Saudi English Language Teachers in Reading Comprehension Classes

Abstract: The study identified how Saudi schoolteachers perceive reading and comprehension. It also investigated the effect of teachers' willingness and lesson presentation on learners' achievement. A descriptive approach was used, and the sample consisted of 56 teachers. The lesson plan in Broughton et al.'s study was adopted as a model lesson plan. Respondents' responses revealed their poor awareness of the most important activities that facilitate or hinder comprehension. Furthermore, teachers' willingness and readin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Students are not involved in group discussions and usually they are not permitted the opportunity to communicate and interact with their peers and teachers. Similarly, Masadeh (2015) argues that in the Saudi schools, most of the teachers support neither fluent readers nor struggling ones.…”
Section: Research Problemmentioning
confidence: 99%
“…Students are not involved in group discussions and usually they are not permitted the opportunity to communicate and interact with their peers and teachers. Similarly, Masadeh (2015) argues that in the Saudi schools, most of the teachers support neither fluent readers nor struggling ones.…”
Section: Research Problemmentioning
confidence: 99%
“…Saudi EFL teachers also struggle to teach English reading skills and precise reading comprehension adequately (Al-Abiky, 2014;Masadeh, 2015). According to Hazaea and Alzubi (2016), in Saudi English reading classes, teachers direct the reading process, and students generally are passive or marginalized.…”
Section: Overview Of Saudi Efl Teachers' Approaches To Teaching Reading Skillsmentioning
confidence: 99%
“…Overall, in a study examining the performance of Saudi English reading teachers with reference to the processes, procedures, or techniques they employ in English reading classes, Masadeh (2015) found that Saudi EFL teachers (a) consider reading as the decoding of words into speech and as students reading isolated words, instead of making sense of the text; (b) do not equally distribute reading activities between bottom-up and top-down skills, and (c) are not successful in leading productive reading discussions, particularly due to their misconceptions of the questions for text discussion and the timing of the questions asked.…”
Section: Overview Of Saudi Efl Teachers' Approaches To Teaching Reading Skillsmentioning
confidence: 99%
“…On the other hand, most of the previous researchers conducted their studies in order to find out what the difficulty that were facing the students and teachers in reading (Masadeh, 2015) and what teachers' perception on reading method (Ness, 2016). As well as some of them found that reading strategies will help students in improving their reading comprehension.…”
Section: Introductionmentioning
confidence: 99%